INTEGRASI TOTAL QUALITY MANAGEMENT DAN PERFORMANCE MANAGEMENT SYSTEM UNTUK MENINGKATKAN KINERJA KARYAWAN DI PERUSAHAAN MANUFAKTUR - Arif Rachman Putra; Didit Darmawan (Jurnal Ilmiah Satyagraha, 2025)
This study explores the effect of Total Quality Management (TQM) andPerformance Management System (PMS) on employee performance inmanufacturing companies. This study uses a quantitative approach with datacollection through questionnaires. Results show that TQM and PMS have asignificant influence on improving employee performance, with PMS making amore dominant contribution. TQM plays a role through continuous improvementapproaches and employee participation, while PMS supports through resultsbasedevaluation, goal clarity, and feedback. This research providesrecommendations for integrating TQM and PMS in management strategies tosupport sustainable employee performance improvement.